(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
Sacred space is a unique type of architectural environment with historical (temporal), social, cultural, semantic, ritual-functional, spatial-architectural, psycho-emotional (perceptual), memorial, landscape, and ethical aspects that organize a visible and invisible multilayered system. In the course of historical development, such spaces built the spatial structure of the city and functioned as a center of socio-spatial interactions, collective memory, and identity. Sacred territories have undergone a complex evolutionary path. Cultural, political, and social changes have led to transformations and changes in functional purpose, as well as significant destruction. Each historical stage has led to changes or the loss of sacred function, creating new semantic and architectural-spatial layers. Given the current challenges, the regeneration of sacred spaces requires a balanced approach that includes not only functional adaptation or restoration, but also a careful analysis of historical and spatial layers. A scenario-based, variable, and flexible approach is aimed at integrating a new purpose into the sacred space without losing its spiritual and semantic meanings. The choice of the project concept for the scenario is justified by a number of factors that will set the limits of permissible intervention in the sacred environment. Depending on the types of sacred spaces, their historical evolution, architectural and functional transformations, state of preservation, architectural and urban planning potential, there is a need to structure approaches to their regeneration. The study considers the following typology of project scenarios for the regeneration of sacred spaces: conservation-museum, hybrid sacred-public, adaptivecultural, landscape-memorial. Confirmation of the feasibility of design scenarios for the regeneration of sacred spaces predicts sustainable development, taking into account the visible and invisible layers of the architectural environment. The prospects for the development of the scenario method will provide the prerequisites for the creation of scientifically sound design solutions for the restoration of sacred space.